CFRP Strengthening of Circular Geo-Polymer Concrete Slab with and without Openings - Ali, Haider Raad; Al Amli, Ali Sabah (Engineering, Technology & Applied Science Research, 2025)
The current study investigates the eco-friendly concrete and specifically Geopolymer Concrete (GPC), and its behavior in reinforced concrete circular slabs both with and without openings. It also examines GPC strength utilizing Carbon Fiber Reinforced Polymer (CFRP) sheets under punching shear. Slag-based GPC was used to cast the slabs. The experimental part included testing six circular slabs divided into two groups with a diameter of 700 mm and a thickness of 70 mm, and a cast circular column with dimensions of 150 x 150 mm at the top face in the middle. The slab components of these samples were strengthened with a distorted 8 mm diameter dispersed across the section of 75 mm c/c. The circular column was reinforced by 5Ø6mm bars, with a 2Ø6@50mm tie to prevent local failure in the column before the slab. The investigated experimental variables included the column location and the strengthening schemes. Measurements were made for the first cracking load, mid-span vertical deflections, and ultimate load capacity. Also, the crack patterns were marked, and the failure mode was observed. Furthermore, the mechanical properties of the slag-based GPC were studied. The results showed that the modulus of rupture and modulus of elasticity were about 3.2 and 29725 Mpa, respectively, and the compressive Strength (fcu) about 45 Mpa. Each slab's initial crack appeared at a load between 23 and 50 kN of its ultimate capacity.